Predicting the Productivity of China’s Building Sector and the Elements that Affect it Using the DEA-Tobit Framework - Guang Cheng (Journal of Digital InformationManagement, 2024)
The total output value of the construction industry, a pillar industry of China, is continuously growing with the expansion of the production and operation scale of Chinese construction enterprises. The extensive high-input mode has promoted the economic growth of the construction industry. Despite the fruitful and outstanding results, production inefficiency has become especially prominent. Though developing rapidly, China’s construction industry possesses fewer ecological investments, accompanied by low environmental awareness and little importance to environmental protection, constantly failing to eliminate high energy consumption, high investments, and high emissions. In addition, the contradiction between the economic growth of the construction industry and the ecological environment remains evident. In this paper, the production efficiency of China’s construction industry was transversely and longitudinally measured using the DEA-Malmquist index method, followed by a further analysis of the factors influencing the production efficiency of China’s construction industry based on the Tobit regression model. The results show that the average production efficiency of China’s construction industry is the highest in the East, moderate in the West, and lowest in the centre. The number of construction enterprises, per capita capital, industrial structure, the proportion of state-owned capitals, and GDP are significant at 1%, 10%, 1%, 1%, and 1%, respectively. The research results can provide theoretical reference for reasonably establishing an ecological efficiency evaluation system for the construction industry to analyze the differences in environmental efficiency among different provinces and regions, further find out the key factors influencing ecological efficiency, propose the corresponding pertinent policy suggestions, and ultimately improve the ecological efficiency of China’s construction industry.